Kesiapan Kapal Menghadapi Kondisi Darurat - Rudi Handoko; Adenan Suhalis (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2020)
All parties concern with high number of marine transportation accidents in Indonesia caused by noise and stress at work. Therefore, it is very necessary for every crew to aware of the implementation of safety standards when working. It is expected, by preparation to face the emergency situation in the ship, that any accident could be handled. In this study, twelve hypotheses were developed and the population was the crew using random sampling to decide 109 people as the respondents. The data analysis technique was using correlation, regression and hypothesis testing. The results show that a) there are direct and indirect effect of stress at work on readiness for emergency situations, b) there are direct and indirect effect of work safety on readiness for emergency situation, c) there is a total effect of noise on emergency preparation, d) there is a total effect of stress at work on emergency preparation, e) there is a simultaneous effect of noise and stress at work on work safety, and f) there is a simultaneous effect of noise and stress at work to prepare dealing with Emergency situation.